Pneumococcal carriage, density, and co-colonization dynamics: A longitudinal study in Indonesian infants. (September 2019) - Murad, Chrysanti; Dunne, Eileen M.; Sudigdoadi, Sunaryati; Fadlyana, Eddy; Tarigan, Rodman; Pell, Casey L.; Watts, Emma; Nguyen, Cattram D.; Satzke, Catherine; Hinds, Jason; Dewi, Mia Milanti; Dhamayanti, Meita; et al.
Highlights: Eighty-five percent of infants carried pneumococcus at least once during the first year of life. Carriage duration was longer for the first acquisition compared to subsequent episodes. Pneumococcal density is affected by antibiotic exposure and respiratory infection. Pneumococcal density decreases during a carriage episode. Most infants carried a single serotype at a time. Abstract: Objectives: Nasopharyngeal carriage of Streptococcus pneumoniae underpins disease development and transmission. This study was performed to examine pneumococcal carriage dynamics, including density and multiple serotype carriage, in Indonesian infants during the first year of life. Methods: Two hundred healthy infants were enrolled at 2 months of age. Eight nasopharyngeal swabs were collected from enrolment until 12 months of age. Pneumococci were detected using quantitative PCR and serotyped by microarray. Regression models assessed factors influencing pneumococcal carriage and density. Results: Eighty-five percent of infants carried pneumococci at least once during the study. The median age at first acquisition was 129 days (interquartile range 41–216 days). The median duration of carriage was longer for the first pneumococcal acquisition compared with subsequent acquisitions (151 days vs. 95 days, p  < 0.0001). Of the 166 infants who carried pneumococci during the study, the majority (63.9%) carried a single pneumococcal serotype at a time. Pneumococcal carriage density was higher when upper respiratory tract infection symptoms were present, lower during antibiotic usage, decreased with age, and tended to decrease over time during a carriage episode. Conclusions: The majority of Indonesian infants carry pneumococcus at least once during the first year of life. Pneumococcal carriage is a dynamic process, with pneumococcal density varying during a carriage episode.